Microalgal whole-cell biomarkers as sensitive tools for fast toxicity and pollution monitoring of urban wet weather discharges. (February 2019) - Gosset, Antoine; Durrieu, Claude; Barbe, Pauline; Bazin, Christine; Bayard, Rémy
Abstract: Urban wet weather discharge (UWWD) management is an important issue. UWWD often represents a significant source of pollution in all aquatic bodies. The occurrence of this pollution is difficult to predict due to the variability of storm events and the unknown contents of urban watershed leached out by rain. Previous studies have tried to demonstrate the ecotoxic impact of UWWD. However, most of them merely highlight the limitations of classic monospecific bioassays, given the high dilution of micropollutants or the presence of nutrients masking toxic effects. Overcoming this problem is therefore of great interest. In this study, we demonstrated the utility of a battery of biomarkers (e.g. membrane permeability, chlorophyll fluorescence, esterase and alkaline phosphatase activities) on the microalgae Chlorella vulgaris to detect the toxic effects of 7 UWWD samples after short exposures (2 and 24 h). These biomarkers are linked to microalgal life traits. Complementarily, monospecific bioassays were carried on Pseudokirchneriella subcapitata, Chlorella vulgaris, Daphnia magna and Heterocypris incongruens to compare their sensitivity to the UWWD samples. No toxic effect was detected in any of the bioassays. Yet, algal biomarkers indicated a disturbance in microalgae physiology, and particularly a perturbation of chlorophyll fluorescence, which was observed in all of the samples tested. While algal membrane permeability was affected by only one UWWD, these two enzymatic activities were stimulated or inhibited depending on the sample. Finally, this study demonstrates the sensitivity of algal biomarkers and the need to develop new, fruitful approaches to characterizing UWWD toxicity. Graphical abstract: Highlights: Urban wet weather discharge often contains residual micropollutant concentrations. A newly developed algal biomarker battery was applied to UWWD samples. Algal Autofluorescence appeared to be particularly sensitive. These biomarkers could be employed for UWWD in situ monitoring (biosensors).